Baduanjin exercise modulates the hippocampal subregion structure in community-dwelling older adults with cognitive frailty - Wan, Mingyue; Xia, Rui; Lin, Huiying; Ye, Yu; Qiu, Pingting; Zheng, Guohua (Frontiers in Aging Neuroscience, 2022)
Background: Regular Baduanjin exercise intervention was proven to be beneficial in improving the cognitive ability and physical performance of older adults with different health conditions but was shown to have varying effects on the structural plasticity of the hippocampus. This study aimed to explore the modulation of hippocampal subregions as a mechanism by which Baduanjin exercise improves cognitive frailty in older adults. Methods: A total of 73 community-dwelling older adults with cognitive frailty were recruited and randomly allocated to the Baduanjin exercise training group and usual physical activity control group. The participants in the Baduanjin exercise training group participated in a 24-week Baduanjin exercise intervention program with an exercise frequency of 60 minutes per day, three days per week. Cognitive ability and physical frailty were assessed, and MRI scans were performed on all participants at baseline and after 24 weeks of intervention. Results: After 24 weeks of intervention, the MoCA and MQ scores of the Baduanjin training group were significantly higher than those of the control group (P<0.05), while the EFS score of the Baduanjin training group was significantly lower than that of the control group (P<0.05). The differences in the left parasubiculum, HATA, right CA1 and presubiculum volumes from baseline to 24 weeks after the start of intervention in the Baduanjin training group were significantly greater than those in the control group (P<0.05/12). Further analysis showed that the changes in right CA1 volume were positively correlated with the changes in MoCA and MQ scores (r=0.510, P=0.015; r=0.484, P=0.022;), the changes in right presubiculum and left parasubiculum volumes were positively correlated with the changes in MQ (r=0.435, P=0.043) and picture test scores (r=0.509, P=0.016), respectively, and the changes in left parasubiculum and HATA volumes were negatively correlated with the changes in EFS scores (r=-0.534, P=0.011; r=-0.575, P=0.005) in the Baduanjin training group, even after adjusting for age, sex, years of education and marital status. Conclusion: A 24-week Baduanjin exercise intervention effectively improved cognitive ability and reduced physical frailty in community-dwelling older adults with cognitive frailty, and the mechanism might be associated with modulating the structural plasticity of the hippocampal subregion.